Influence of fluid balance on postoperative outcomes after hepatic resection in patients with left ventricular diastolic dysfunction - Shin, Jungho; Suh, Suk-Won (Frontiers in Surgery, 2022)
Objective The maintenance of low central venous pressure (CVP) during hepatic resection is associated with a reduction in estimated blood loss. After completion of the hepatic parenchymal transection, fluid is rapidly administered to replace the surgical blood loss and fluid deficit to prevent subsequent organ injury risk. However, this perioperative fluid strategy may influence on the postoperative outcomes of patients with left ventricular diastolic dysfunction (LVDD) who cannot tolerate volume adjustment. Method A total of 206 patients with who underwent hepatic resection between March 2015 and February 2021 were evaluated. LVDD was defined according to the American Society of Echocardiography and the European Association of Cardiovascular Imaging 2016 recommendations as LVDD (group A, n = 39), or normal LV diastolic function and indeterminate decision (group B, n = 153). We compared the clinical outcomes of patients between two groups, and then analyzed the risk factors for postoperative complications. Result Postoperative acute kidney injury (AKI, 10.3% vs. 1.3%, P = 0.004) and pleural effusion or edema (51.3% vs. 30.1%, P = 0.013) were more common in group A than in group B. Further, creatinine levels from postoperative day 1 to day 7 were significantly higher and daily urine outputs at postoperative day 1 (P = 0.038) and day 2 (P = 0.025) were significantly lower in group A than in group B. LVDD was the only significant risk factor for postoperative AKI after hepatic resection (odds ratio, 10.181; 95% confidence interval, 1.570–66.011, P = 0.015). Conclusions The rates of renal dysfunction and pulmonary complications after hepatic resection are higher in patients with LVDD than in those with normal LV diastolic function. Thus, these patients require individualized fluid management.